Pengaruh Metode Bermain Peran terhadap Penguasaan Konsep Bilangan Anak Usia Dini Usia 4-5 Tahun di TK Inomata, Kec. Suwawa Selatan - Sri Cindi Patuti; Mita Sari; Ravika Latedu; Deliyawati Hairi; Iyutri Ladiku; Indri Handayani H. Dulusea; Dea Prananda (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study aims to evaluate the impact of role-playing methods on learning interest and number concept mastery in 4-5-year-old children at TK Inomata, Suwawa Selatan District, Bone Bolango Regency. The approach used is a quantitative experimental method with purposive sampling of 8 children, and data collection was carried out through observations of aspects such as enjoyment, focus, activity, and enthusiasm, using a 1-4 scale. The results show that the average learning interest score using the traditional method was only 5.86 (low category), with details: enjoyment 1.71, focus 1.29, activity 1.29, and enthusiasm 1.57. In contrast, the role-playing method of trading/store games showed an average score of 13.86 (very good category), with details: enjoyment 3.57, focus 3.43, activity 3.29, and enthusiasm 3.57. This significant improvement indicates that the role-playing method is more effective in creating interactive, enjoyable, and contextual learning, as well as supporting number comprehension through everyday activity imitation and social skill development. It is recommended to routinely apply this method in early childhood education (PAUD) with adequate teaching aids, as well as involve parents to support the holistic development of children during the golden age.